Evaluation of Sociodemographic Characteristics and Effects of Sensory Stimulation for Management of Acute Stroke Syndrome in Children - Abdul Hye, Mohammad; Rahman, Md Shamsur; Hossain, Md Iqbal; Ahmed, Shuperna (Medicine Today, 2024)
Introduction with Objective: In this study our main goal is to assess the sociodemographic characteristics of acute stroke syndrome in children and effect of sensory stimulation for management of acute stroke. Materials and Methods: This randomized control trial study conducted at Magura Medical College Hospital, Magura from January 2021 to December 2023. During experiment, in study group was 43 patients & 42 patients in control group. Children in study group were given sensory stimulation therapy while those in control group received no sensory stimulation. Result: during the study, highest number of the patients in study and control group belong to 2 months to 1 year’s age group, (n=24) and (n=27). 57% patients from urban and 43% from rural. 76% patients had ischemic stroke and 24% had hemorrhagic stroke. Also, GCS score improved significantly after two weeks of sensory stimulation in study group. Conclusion: From our study we can conclude that, early sensory stimulation has been shown to have significant effects, both beneficial and detrimental, on stroke size and functional outcome. Further study is needed for better outcome. Medicine Today 2024, Vol.36 (2): 124-126